"From caged birds to women with wings": A perspective on consumption practices of new middle-class Indian women. (25th February 2020) - Rangwala, Shenaz; Jayawardhena, Chanaka; Saxena, Gunjan
Abstract : Purpose: This study aims to explore consumption practices of new middle-class Indian women to explicate how they are challenging traditional social norms and redefining their identity through their consumption practices. Design/methodology/approach: A total of 32 semi-structured and photo-elicitation interviews were conducted with new middle-class women between the age group of 23 and 40 years in India. Findings: This study illustrates how the doing of consumption practices that involve creating, controlling, knowing and transforming is enabling new middle-class Indian women to undo gender disparities embedded in hegemonic patriarchal social order. Also, the study provides new insights into how class and symbolic capital intersect gender to redefine middle-class women's feminine self. Research limitations/implications: This study specifically illustrates how new middle-class women are using consumption practices to uplift their position in household; bring about new modes of social interface; and identity expression and a reversal in gender roles. Practical implications: The conflation of women's independence with consumerism underlines the need for marketers to position consumer goods in a manner that strengthens women's self and alleviates cultural perceptions of women as subordinate to men in the household. Indian market has considerable growth potential for publicly visible brands that affirm the elevated social status of women and allow them to effectively demonstrate their capital resources. Originality/value: An under-researched consumer segment is explored by focusing particularly on the intersection of discourses of women's individuality with that of their consumption practices. Additionally, pioneering use of photo-elicitation technique coupled with hermeneutic approach enabled to elicit effectively women's reflections on their behaviours, values and motivations underlying their consumption practices.